2021
DOI: 10.1002/cncr.34052
|View full text |Cite
|
Sign up to set email alerts
|

Providing cessation treatment to every oncology patient who smokes: An essential component of cancer care

Abstract: Patients with cancer who smoke can gain significant benefits from quitting, including lower cancer and all‐cause mortality. It is imperative for oncology clinicians to address smoking cessation with all patients with cancer who smoke, both for their overall health and to improve cancer outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These results highlight the significance of providing smoking cessation education to cancer survivors and emphasize that quitting is never too late. Given the increased risk of cancer progression, recurrence, second primary malignancies, and inferior treatment outcomes, smoking cessation should be a top priority in managing cancer patients who smoke ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results highlight the significance of providing smoking cessation education to cancer survivors and emphasize that quitting is never too late. Given the increased risk of cancer progression, recurrence, second primary malignancies, and inferior treatment outcomes, smoking cessation should be a top priority in managing cancer patients who smoke ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of smoking among patients with cancer underlines the need for timely tobacco treatment. Smokers are more likely to attempt to quit immediately after a diagnosis, suggesting that a diagnosis can serve as a teachable moment for smoking cessation, in which the motivation to quit is temporarily increased [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have found that gain-framed messages are more effective at conveying the short-term benefits of cessation [ 19 ]; however, there has been limited investigation into whether this strategy is as effective among patients with a recent cancer diagnosis. This is an important area of inquiry as quitting can result in important short-term benefits by reducing cancer treatment side effects, as well as improving overall energy levels and reducing levels of stress [ 4 , 8 ]. Determining whether to frame the benefits of cessation or the costs of not quitting on these short-term outcomes can act as an important mechanism for motivating cessation and trial enrollment during cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…There have been substantial efforts to make evidencebased tobacco dependence treatments available through the healthcare delivery system (Baker et al, 2021;Cook et al, 2021;Fiore et al, 2021;Fiore et al, 2008;Hurt et al, 2009;Ramsey et al, 2020;Sarna et al, 2020;Trapskin et al, in press;Williams et al, 2021). Unfortunately, these efforts have not typically extended to behavioral health care systems that uncommonly provide cessation treatment programs.…”
Section: Introductionmentioning
confidence: 99%